Experimental investigation of CO2 storage and oil production of different CO2 injection methods at pore-scale and core-scale. (1st September 2022) - Hao, Yongmao; Li, Zongfa; Su, Yuliang; Kong, Chuixian; Chen, Hong; Meng, Yang
Abstract: The CO2 storage and oil production of different CO2 injection schemes via laboratory experiments was investigated in this study. Microfluidic equipment was upgraded to increase its working pressure above the miscible pressure of the CO2 /oil system. Microfluidic experiments of immiscible CO2 injection, miscible CO2 injection, water injection, and water alternating CO2 (WAG) injection were conducted. Affected by buoyancy subject to gas phase, apparent gas overriding and flow stratification were observed under immiscible conditions in porous media. Miscible CO2 injection eliminated the influence of buoyancy, thereby expanding the CO2 storage area and enhancing oil production. Non-uniform miscibility was observed during miscible CO2 injection, caused by connate water, tiny pores, and differential pressure. Water flooded most areas in the porous media, but small dispersed oil such as droplet oil and film oil remained in the water-flooded pores, resulting in low oil washing efficiency. The strong Jamin effect in the water-flooded area, caused by the dispersion of the remaining oil, inhibited the gas overriding and expanded the scope of CO2 flow in WAG, thereby increasing the oil production. However, the water slug occupied a large pore volume and drove out the CO2 stored at the beginning stage, resulting in low CO2 storage. The core flooding experiments were conducted to quantitatively evaluate the CO2 storage and oil recovery of different CO2 injection methods. Miscible injection produced 20.5%, 12.2%, and 2.9% more oil than immiscible CO2 injection, water flooding, and WAG. Besides, the produced gas by miscible CO2 injection was 46.5% and 47.6% lower than that of immiscible CO2 injection and WAG, respectively. Highlights: Upgraded microfluidic equipment for miscible CO2 flooding. Visualization of pore-scale CO2 flow patterns in porous media. Visualization of the state of pore-scale CO2 storage for different CO2 injection methods. Multi-scale comparison of CO2 storage and EOR for different CO2 injection methods. Suggestions for CO2 injection schemes considering CO2 storage/EOR.